PENGEMBANGAN MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLETING, EXTENDING (CORE) BERBASIS GOOGLE SITES SEBAGAI PEMBAHARUAN PEMBELAJARAN MATEMATIKA PADA SEKOLAH MENENGAH PERTAMA KELAS 8 MATERI BANGUNG RUANG SISI DATAR - Hafidho Mufidah; Ifadatul Lailiyah; Ulfhatur Rohmah; Sherly Ida Amitha; Elly Puspitarini; Imron Fauzy (Cartesian: Jurnal Pendidikan Matematika, 2022)
In this modern era, developments are very rapid in various fields, such as the fields of politics, economics, education, and technology. The development of technology has a very big influence, especially in the field of education. The purpose of this study was to determine the results of the development of the Connecting, Organizing, Reflecting, Extending (CORE) learning model based on Google Sites as a renewal of mathematics learning in Grade VIII Junior High Schools. Where the method used to describe and describe the data is by analyzing previous studies that have existed through the collection of references from previous journals. The results of data analysis using qualitative data analysis techniques state that in learning using Google Sites, teachers can easily add learning materials in pictures, videos, and assessments; These features can be designed with the CORE (Connecting, Organizing, Reflecting and Extending) learning model. The stages carried out are the process of taking mathematics learning online and offline accompanied by interactions between teachers and students using the comments column provided by the teacher on the google sites site page, while the interactions carried out offline are discussions or questions and answers. One of the advantages of Google sites is that it makes it easier for students to learn